Extracorporeal Shock Wave Therapy for Children and Adolescents Diagnosed with Osgood Schlatter Disease to Reduce Knee Pain: Systematic Review - Tamboosi, Mohammad; Alharthi, Hashim; Bukhari , Abdulaziz Bukhari; Alsulami , Abdulrahman; Hawari, Waleed; Alahmadi, Yazeed; Alshahrani, Rayan; Alshamrani, Rayan (J Med Rehab Sci, 2024)
Aim: The current systematic review aimed to investigate the effectiveness of ESWT on children and adolescents diagnosed with OSD to reduce their knee pain. Method: An electronic search for studies about ESWT on patients with OSD that were published in English in different databases (CINAHL, PubMed, MEDLINE, Scopus, and PEDro). National Heart, Lung, and Blood Institute’s Quality assessment tool was used to evaluate the included studies. Results: According to the search strategy, from 2807 articles, only 2 studies (retrospective cohort and RCT) were selected for the current review, with a total of 34 subjects (20 Males and 14 Females) diagnosed with OSD participated to be treated with ESWT. They were aged between 12 to 29 years old. all participants were suffering from pain due to OSD. Conclusion: The available evidence suggests that there is a promising effect of using ESWT for patients diagnosed with OSD to reduce their pain. However, the paucity of evidence prevents drawing firm conclusions, necessitating more studies to be conducted for a definite conclusion.